Do pelvic floor muscle exercises reduce postpartum anal incontinence? A randomised controlled trial. (7th June 2016) - Johannessen, HH; Wibe, A; Stordahl, A; Sandvik, L; Mørkved, S
Abstract : Objective: To evaluate the effect of pelvic floor muscle exercises (PFME) for postpartum anal incontinence (AI). Design: A parallel two‐armed randomised controlled trial stratified on obstetrical anal sphincter injury with primary sphincter repair and hospital affinity. Setting: Ano‐rectal specialist out‐patient clinics at two hospitals in Norway. Population: One hundred and nine postpartum women with AI at baseline. Methods: The intervention group received 6 months of individual physiotherapy‐led PFME and the control group written information on PFME. Changes in St. Mark's scores and predictors of post‐intervention AI were assessed by independent samples t ‐tests and multiple linear regression analyses, respectively. The study was not blind. Main outcome measures: The primary outcome measure was change in AI symptoms on the St. Mark's score from baseline to post‐intervention. Secondary outcome measures were manometry measures of anal sphincter length and strength, endoanal ultrasound (EAUS) defect score and voluntary pelvic floor muscle contraction. Results: There was a significant difference in the reduction of St. Mark's scores from baseline to post‐intervention in favour of the PFME group (−2.1 versus −0.8 points, P = 0.040). No differences in secondary outcome measures were found between groups. Baseline St. Mark's, PFME group affinity and EAUS defect score predicted post‐intervention St. Mark's score in the imputed intention‐to‐treat analyses. The analysis on un‐imputed data showed that women performing weekly PFME improved their AI scores more than women in the control group did. Conclusions: Our results indicate that individually adapted PFME reduces postpartum AI symptoms. Tweetable abstract: Performing regular pelvic floor muscle exercises may be an effective treatment for postpartum anal incontinence. Tweetable abstract: Performing regular pelvic floor muscle exercises may be an effective treatment for postpartum anal incontinence. This article includes Author Insights, a video abstract available athttps://vimeo.com/rcog/authorinsights14145 .